2000
DOI: 10.1002/1098-2280(2000)35:4<270::aid-em2>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity biomonitoring in coal regions using wild rodentCtenomys torquatus by Comet assay and micronucleus test

Abstract: Coal is a mixture of a variety of chemicals, especially hydrocarbons, which may give rise to polycyclic aromatic hydrocarbons (PAH). Many PAH compounds produce mutagenic and carcinogenic effects. The quality of mineral coal in Rio Grande do Sul (RS) is low and it is typically obtained by stripping operations; it represents approximately 87% of the Brazil reserves. This report concerns the application of the Comet assay to Ctenomys torquatus to detect the effects of coal, comparing the results with a micronucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Randomly selected cells (300 cells from each of three replicate slides, total = 900 cells) were analyzed per COR concentration. Cells were visually scored regarding damage, divided into five classes, and the DNA damage index was calculated as described by Collins et al (1995) and da Silva et al (2000). Doxorubicin (0.2 μg/mL) was used as positive control and 1% DMSO as solvent control.…”
Section: Methodsmentioning
confidence: 99%
“…Randomly selected cells (300 cells from each of three replicate slides, total = 900 cells) were analyzed per COR concentration. Cells were visually scored regarding damage, divided into five classes, and the DNA damage index was calculated as described by Collins et al (1995) and da Silva et al (2000). Doxorubicin (0.2 μg/mL) was used as positive control and 1% DMSO as solvent control.…”
Section: Methodsmentioning
confidence: 99%
“…It is acknowledged that age and gender are important biological parameters that now are required to be provided in study designs, analyses, and reporting in experimental animal and human studies [18,19]. However, only a few biological monitoring studies have been reported showing that age and sex can influence DNA damage from exposure to environmental pollutants [20,21]. Heuser et al have shown that adult females are the principal population affected by air pollutants from vehicle emissions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Heuser et al have shown that adult females are the principal population affected by air pollutants from vehicle emissions [20]. In a study comparing the level of damaged cells in adult, sub-adult, and juvenile rodents to identify possible relationships between age and DNA impairment, increases in the level of damaged cells associated with age were found for wild rodents in coal regions [21]. In a study assessing micronucleus formation in rats after chronic exposure to DEP, no sex-based differences in MN frequency were observed [22].…”
Section: Introductionmentioning
confidence: 99%
“…A number of wild species have been used in the monitoring of environmental contamination [ 2 , 11 – 14 ], but only a few studies have employed mammals [ 15 17 ]. Studies on the association between exposure to pollutants and changes in the physiology and population dynamics of different mammals, as well as on how pollutants cause habitat loss and disease, and alter natural cycles, are therefore all needed [ 18 ].…”
Section: Introductionmentioning
confidence: 99%